Does Activating Sick-Listed Workers Work? Evidence from a Randomized Experiment - Kai Rehwald; Michael Rosholm; Benedicte Rouland (Institute for the Study of Labor (IZA), 2016)
Using data from a large-scale randomized controlled trial conducted in Danish job centers, this paper investigates the effects of an intensification of mandatory return-to-work activities on the subsequent labor market outcomes for sick-listed workers. Using variations in local treatment strategies, both between job centers and between randomly assigned treatment and control groups within a given job center, we compare the relative effectiveness of alternative interventions. Our results show that the use of partial sick leave increases the length of time spent in regular employment and non-reliance on benefits, and also reduces the time spent in unemployment. Traditional active labor market programs and the use of paramedical care appear to have no effect at all, or even an adverse effect.
Keywords: J68; C93; I18; 330; long-term sickness; vocational rehabilitation; treatment effects; randomized controlled trial